Movimentação de cálcio em colunas de solo tratadas com carbonato e sulfato de cálcio - Dias , Luiz Eduardo; A S Ferreira , Francisco; Ribeiro , Antônio Carlos; da Costa , Liovando Marciano (Revista Ceres, 2025)
Soil columns, 30 cm high, of a clayey, red-yellow latosol were treated with two levels of calcium, as calcium carbonate or calcium sulfate, in the first 5 cm of depth, at rates equivalent to one and two times the liming requirement.